A Gestalt perspective on Manichaean worldviews and individuals’ engagement in violence: the case of the Italian far left - Grillo, Giulia (Frontiers in Political Science, 2025)
Besides socio-political and economic factors, extant research contends that Manichaean worldviews, characterized by mutually exclusive dichotomies such as ‘good-bad’, are the main driver influencing individuals’ decision to use violence against others. Furthermore, extant scholarship identifies ideologies, populism, and conspiracy theories as the three originators of Manichaean worldviews. However, the findings from my research, carried out between 2018 and 2023, challenge these arguments. Using narrative analysis, this article examines personal stories of a group of Italian former far-left militants, who participated in the violent campaign of the so-called ‘Years of Lead’. Far-left and far-right ideologies strongly influenced Italian socio-political movements of the time. Thus, this paper explores whether Manichaean perspectives informing far-left militants’ decision to resort to violence originated from far-left ideologies or whether they existed independently of these ideologies. I develop this analysis through the lens of Gestalt psychology, which considers human behavior as resulting from how our minds understand the relation between components of our surrounding environment. While confirming relations between Manichaean worldviews and violence, this paper finds that Manichaean perspectives result from human cognitive processes and are then rigidified by ideological narratives. This work provides important insight to better understand radicalization and engagement in violence, and to develop appropriate responses to prevent it.